Assessing health systems in unrecognised states: lessons from the field. (22nd August 2018) - Garber, Kent; Aboulian, Armen; Nalbandian, Dickran; Abrahamyan, Arina; Danielyan, Artak; Amirjanian, Artak; Shekherdimian, Shant
Abstract : Good data are critical to improving the health of these overlooked populations